Seasonal variations in the diet of the Indian oilsardine, Sardinella longiceps Valenciennes off Cochin, Kerala - Remya, R; Vivekanandan, Elayaperumal; Manjusha, Ushadevi; Nair, Preetha G (Indian Journal of Fisheries, 2013)
Seasonal fluctuations in the food of the oilsardine Sardinella longiceps landed by ring seines from the inshore waters off Cochin were studied during 2010. S. longiceps is chiefly a plankton feeder with diatoms, dinoflagellates and zooplankton appearing in the diet in decreasing order of abundance. During pre-monsoon (February-May), Pleurosigma was present in 70% of the stomachs analysed followed by Thalassiosira, Biddulphia and Coscinodiscus. During monsoon season (June-September), 87.5% of the stomachs contained Coscinodiscus followed by Thalassiosira and Pyrophacus. During post-monsoon (October- January) again, the frequency of occurrence of Pleurosigma (74.2%) was higher followed by Biddulphia and Thalassiosira. Zooplankton, represented by tintinnids and copepods, were present in the diet throughout the year, but in relatively less number of stomachs. Higher feeding activity was observed during monsoon (June-September), which coincided with maximum spawning activity.